Transformational Leadership of Kiai: Efforts to Strengthen Teacher Performance at the Hidayatul Mubtadiien Islamic Boarding School in South Lampung - Muhammad Abdul Aziz; Rahmat; Fathi Hisyam Panagara (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The quality of education in Indonesia faces serious challenges related to low teacher competency, and teacher performance in Islamic boarding schools (pesantren) is inextricably linked to the way leadership authority shapes commitment, discipline, and organizational rhythm. This article aims to explore the articulation of the kiai's transformational leadership in improving the performance of educators at the Hidayatul Mubtadiien Islamic Boarding School in South Lampung. Using a qualitative single-case study method, data were collected in depth to examine the dynamics of leadership in the field. The results show that the dimensions of ideal influence, inspirational motivation, and individual attention are operationalized through the integration of strong religiosity values ​​as a form of spiritual